Educação ambiental e matemática: uma proposta de ensino sob uma abordagem transdisciplinar a partir de revisões de literatura - Pacheco, Caiane de Lima (2023)
The global environmental crisis that we are experiencing reached a critical point that can no longer be ignored and in order to counter it many reparation acts and transformations have been proposed on regional and global levels. In this way, the Environmental Education (EE) emerges as an opportunity to expand critical awareness and the individual and collective concern with environmental and social issues, and the school, an organized space to build citizenship formation, is the ideal place for the insertion of these questions, including in the discipline of math. Thus, this research aims to understand how EE has been inserted in math classes in High School (EM), in order to elaborate a Teaching Proposal to guide a math work that favors EE over a transdisciplinary approach, the most suitable to deal with complex problems such as those involving EE. For this purpose, we developed a qualitative bibliographical research, we made two literature reviews on PhD thesis and master's dissertations from the Coordination for the Improvement of Higher Education Personnel (Capes) database, one about EE and mathematical teaching and the other about mathematical teaching and transdisciplinarity, in order to subsidize the proposition of the Teaching Proposal. Continuing, we evaluated the applicability of the Proposal through the analysis of the answers of five math teachers, with experience in EM, of a previously established questionnaire and finally we restructured the material based on the triangulation of the answers obtained and the information already collected. The reviews pointed to the scarcity of works that integrate EE and math in the EM, the relevance of transdisciplinary proposals that deal with such subjects, the teachers difficulty in working content in a contextualized way and fulfilling the goals set out in the curriculum, and the necessity to bring beforehand arguments/dynamics that encourage teachers to address issues that take them out of their comfort zone, in order to enable a better adhesion to the action. Thus, in the conception of the proposal, these assertions were taken into account. As a result, we showed that it is possible to work with the tripod math – EE – transdisciplinarity in order to emphasize the importance of this discipline for the citizenship formation of the students, seeking to implement a curriculum that englobes the reality of the student and walk towards a more a more sustainable and ethical society.